Search Engine Optimisation: Evidence From Pakistan - Ahmed, Irfan; Shahzad, Rana Khurram; ur Rehman, Kashif; Shabbir, Javeria (Asian Academy of Management (AAM), 2013)
This study has two objectives. The first objective is to investigate firm exploitation of search engine optimisation (SEO) techniques with respect to website traffic. The second objective is to report on the searching habits of Internet users. This study uses a qualitative descriptive approach that analyses 15 different case studies of business to business (B2B) and business to consumer (B2C) companies. These companies include nine banks, four telecommunication companies and two automotive companies. The indepth, semi-structured interviews were administered by telephone and/or personal interviews. Additionally, a questionnaire-based survey was administered to Internet users to determine their web use and searching habits. The results demonstrate that firms are currently exploiting SEO at a limited level, that the use of social media is rare and that firms do not consider users' searching habits. This study also reveals that 84% of web users spend up to two hours daily searching the Internet. The dominant search engine (i.e., the engine used by 90% of users) is Google. The use of social sites such as Facebook, Twitter, MySpace and Orkut is high among users (i.e., 85%). This study highlights the opportunities that SEO provides to companies with respect to the use of their corporate website as a strategic marketing tool.